Notes on oil sources for the bee genus Caenonomada(Hymenoptera, Apidae, Tapinotaspidini) Notas sobre fontes de óleos florais do gênero Caenonomada (Hymenoptera, Apidae, Tapinotaspidini) - Antonio J. C. Aguiar; Gabriel A. R. Melo (Revista Brasileira de Entomologia, 2009)
It is reported for the first time oil collecting by bees of the genus Caenonomada on flowers of Plantaginaceae. Females of Caenonomada unicalcarata were observed collecting oil on flowers of Angelonia cornigera, and males and females of Caenonomada bruneri and C. aff. unicalcarata were observed on flowers of Angelonia and Monopera (Plantaginaceae). The record of Caenonomada on Plantaginaceae suggests the use of trichomatic oil glands as a primitive condition in the tribe Tapinotaspidini. Pela primeira vez é reportado a coleta de óleo por Caenonomada em Plantaginaceae. Fêmeas de Caenonomada unicalcarata foram observadas coletando óleo em flores de Angelonia cornigera, e fêmeas e machos de Caenonomada bruneri e Caenonomada aff. unicalcarata em flores de Angelonia e Monopera (Plantaginaceae). O registro de Caenonomada em Plantaginaceae sugere uma condição mais primitiva para o uso de glândulas tricomáticas de óleo na tribo Tapinotaspidini.